Exploring the exercise intensity equivalent to the anaerobic threshold in patients with acute myocardial infarction based on the 6-minute walk test distance - Fan, Yuxuan; Sun, Xiaopeng; Li, Guihua; Wang, Xiaojing; Luo, Qian; Wang, Lemin; Shen, Yuqin; Fan, Zhiqing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to evaluate the correlation between aerobic exercise intensity based on the 6 min walk test (6MWT) and the anaerobic threshold (AT)-based equivalent in patients with acute myocardial infarction (AMI). The feasibility of using the 6MWT for exercise prescription in primary care settings was also investigated.MethodsA retrospective analysis was conducted on data from AMI patients, including statistics on all values of the cardiopulmonary exercise test and 6MWT parameters.ResultsRegression analysis showed that the regression equation based on 6MWD exercise intensity (EI6MWD) could predict AT-based exercise intensity (EIAT). Moreover, EI6MWD correlated with EIAT in 91.9%–93.0% of patients' EI6MWD, with AMI equivalent to the EIAT model.ConclusionsThe findings suggest that the anaerobic threshold in AMI patients corresponds to 91.9%–93.0% of the distance covered during the 6MWT. Thus, the 6MWT is a feasible tool for developing exercise prescriptions in primary care hospitals.